Efficient Grain Production in the Context of Digital Agricultural Technologies - Subaeva, Asiya; Khudyakova, Elena; Zaruk, Natalia; Stepantsevich, Marina; Gorbachev, Mikhail (Journal of Environmental Accounting and Management, 2026)
The relevance of the study is due to the need for monitoring grain production and insufficient development of theoretical, content-technological and scientific-methodological aspects of the use of digital technologies in agriculture. The main purpose of the research is to monitor the state of grain production in Russia and to develop practical recommendations for the use of digital technologies in the crop production industry. The article presents the main components of digitalization of the crop production industry in general and grain production in particular. It has been established that the modern period of development of grain production in the context of the digital economy and the accelerated development of scientific and technological progress combines a complex of various phenomena, suggesting a significant strengthening of the role of science in the development of society. The presented recommendations are aimed at introducing digital technologies into the process of grain production and adapting agribusiness to new conditions of technological production.